Preparation method and application of functional water-absorbing chitosan material

By introducing groups such as quaternary ammonium salts and sulfonic acid into chitosan and crosslinking with aldehyde triazine quaternary ammonium salt crosslinking agent, functionalized water-absorbing chitosan materials are prepared, which solves the problem of insufficient adsorption performance of existing adsorbents when treating wastewater containing metal ions such as chromium and copper, and achieves the effect of efficient adsorption of these pollutants.

CN119899286AInactive Publication Date: 2025-04-29JIANGSU TONGNENG NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202510068500.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-29
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When existing adsorbents treat wastewater containing metal ions such as chromium and copper, their adsorption performance is insufficient, making it difficult to effectively remove these pollutants.

Method used

By introducing groups such as quaternary ammonium salts and sulfonic acid into chitosan, functionalized water-absorbing chitosan materials are prepared, and cross-linking reactions are carried out with chitosan using aldehyde triazine quaternary ammonium salt cross-linking agent to form a porous structure of a spatial cross-linking network to improve its water absorption rate and adsorption performance.

Benefits of technology

It significantly improves the water absorption rate and adsorption performance of chitosan materials, can effectively adsorb metal ions such as Cr2O72- and Cu2+, and is suitable for the treatment of metal-containing wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899286A_ABST
    Figure CN119899286A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of chitosan, and discloses a preparation method and application of a functional water-absorbing chitosan material, an aldehyde triazine quaternary ammonium salt cross-linking agent and amino of chitosan are subjected to a cross-linking reaction, hydrophilic quaternary ammonium salt and sulfonic acid are grafted into the chitosan material, and the hydrophilicity of chitosan is remarkably improved. And the aldehyde triazine quaternary ammonium salt cross-linking agent contains three aldehyde groups, and forms a porous structure of a space cross-linked network with the chitosan, so that the water absorption rate is greatly increased. The chitosan material contains functional quaternary ammonium salt cation groups which can form electrostatic interaction with Cr2O7 < 2-> anions, meanwhile, nitrogen atoms in sulfonic acid groups, nitrogen-rich triazine and imidazole structures can generate coordination chelation with metal ions such as Cu < 2 + >, and the equilibrium adsorption capacity of the chitosan material to Cu < 2 + > is improved. The method has a wide application prospect in the field of metal-containing sewage treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chitosan, in particular to a preparation method and application of a functionalized water-absorbing chitosan material. Background Art

[0002] Mining, metallurgy, electroplating and other industries will generate a large amount of metal-containing wastewater during the production process, including copper, mercury, chromium, lead, etc., which are highly toxic and polluting. The current methods for treating these wastewaters are mainly adsorption, precipitation, oxidation-reduction, etc.; in recent years, the development of new adsorbents with low cost and strong adsorption performance has been a research trend.

[0003] Traditional adsorbents mainly include macroporous resins, activated carbon, flocculants, etc. Chitosan is a natural biomass polysaccharide derivative with the advantages of being green, environmentally friendly, widely available, and having good adsorption properties. Functional modification of chitosan can effectively improve its adsorption properties. The patent with announcement number CN113150320B uses 2-acrylamide-2-methylpropane sulfonic acid, laponite, acrylamide, N,N-methylenebisacrylamide, chitosan, etc. as reactants to prepare chitosan-based double network high-strength hydrogels with abundant active sites and a higher specific surface area, which is more conducive to the adsorption of methylene blue. However, it does not show good adsorption properties for metal ions such as chromium and copper. The present invention aims to prepare a functionalized water-absorbing chitosan material containing groups such as quaternary ammonium salts and sulfonic acids to improve the water absorption rate and adsorption properties of chitosan. Summary of the invention

[0004] Technical issues solved

[0005] The invention provides a preparation method and application of a functionalized water-absorbing chitosan material with high water absorption rate and good adsorption performance.

[0006] Technical Solution

[0007] A method for preparing a functionalized water-absorbing chitosan material comprises the following steps: adding 1-2% acetic acid solution and chitosan into a reaction bottle, stirring and dissolving, adding an aldehyde triazine quaternary ammonium salt crosslinking agent, stirring and reacting at a temperature of 60-75°C for 3-8h, precipitating, filtering, washing with water, and drying to obtain the functionalized water-absorbing chitosan material.

[0008] Furthermore, the mass of the aldehyde triazine quaternary ammonium salt cross-linking agent is 5-30% of the mass of chitosan.

[0009] Further, the preparation method of the aldehyde triazine quaternary ammonium salt cross-linking agent comprises the following steps:

[0010] S1. Add tetrahydrofuran, water, sodium hydroxide, sodium 2-chloroethane sulfonate and 4-imidazolecarboxaldehyde to a reaction bottle, stir and dissolve, heat to 40-55°C and react for 4-10 hours, concentrate to remove tetrahydrofuran, add hydrochloric acid solution to adjust the pH to 2-4, add saturated sodium chloride solution and ethyl acetate, extract and separate, concentrate the organic layer to remove ethyl acetate, and recrystallize the product in water to obtain 4-imidazolecarboxaldehyde chlorosulfonic acid intermediate.

[0011] S2. Add N,N-dimethylformamide, cyanuric chloride and 4-imidazolecarboxaldehyde chlorosulfonic acid intermediate into the reaction bottle, stir to react, concentrate to remove N,N-dimethylformamide, and recrystallize the product in ethanol to obtain an aldehyde triazine quaternary ammonium salt crosslinking agent.

[0012] Furthermore, the masses of sodium hydroxide and sodium 2-chloroethane sulfonate in S1 are 45-60% and 180-230% of the mass of 4-imidazolecarboxaldehyde, respectively.

[0013] Furthermore, the mass of the 4-imidazolecarboxaldehyde chlorosulfonic acid intermediate in S2 is 330-400% of the mass of cyanuric chloride.

[0014] Further, the reaction in S2 is carried out at a temperature of 85-100° C. for 12-24 h.

[0015] Technical effect: The present invention uses 4-imidazole formaldehyde, sodium 2-chloroethane sulfonate and cyanuric chloride as reactants to prepare a new type of aldehyde triazine quaternary ammonium salt crosslinking agent, which undergoes a crosslinking reaction with the amino group of chitosan to obtain a hydrophilic quaternary ammonium salt and sulfonic acid grafted into the chitosan material, which significantly improves the hydrophilicity of chitosan. In addition, the aldehyde triazine quaternary ammonium salt crosslinking agent contains three aldehyde groups, which form a porous structure of a spatial crosslinking network with chitosan, and the water absorption rate is greatly increased.

[0016] The chitosan material of the present invention forms a porous structure of a spatial cross-linked network, has a larger specific surface area, a higher water absorption rate, and more adsorption sites, and contains functional quaternary ammonium salt cationic groups, which can react with Cr2O7 2- Negative ions form electrostatic interactions, which significantly improve the chitosan material's ability to resist Cr2O7 2- At the same time, the functional sulfonic acid groups, nitrogen-rich triazine and imidazole structures are grafted onto the chitosan material. The nitrogen atoms in the sulfonic acid groups, nitrogen-rich triazine and imidazole structures can react with Cu 2+ The chitosan material can enhance the chelation of metal ions such as Cu 2+ The equilibrium adsorption capacity of the product is 1.547 W / m. It has broad application prospects in the field of metal-containing wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a high-quality preparation reaction route for aldehyde triazine quaternary ammonium salt crosslinking agent. DETAILED DESCRIPTION

[0018] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0019] Example 1

[0020] S1. Add tetrahydrofuran, co-solvent water, 60 parts by weight of sodium hydroxide, 230 parts by weight of sodium 2-chloroethane sulfonate, and 100 parts by weight of 4-imidazolecarboxaldehyde into a reaction bottle, stir and dissolve, heat to 40°C and react for 10 hours, concentrate to remove tetrahydrofuran, add hydrochloric acid solution to adjust the pH to 4, add saturated sodium chloride solution and ethyl acetate, extract and separate, concentrate the organic layer to remove ethyl acetate, and recrystallize the product in water to obtain 4-imidazolecarboxaldehyde chlorosulfonic acid intermediate.

[0021] S2. Add N,N-dimethylformamide, 100 parts by weight of cyanuric chloride, and 400 parts by weight of 4-imidazolecarboxaldehyde chlorosulfonic acid intermediate into a reaction bottle, stir and react at a temperature of 85° C. for 24 hours, concentrate to remove N,N-dimethylformamide, and recrystallize the product in ethanol to obtain an aldehyde triazine quaternary ammonium salt crosslinking agent.

[0022] Add 1.5% acetic acid solution and 100 parts by weight of chitosan to the reaction bottle, stir to dissolve, add 5 parts by weight of aldehyde triazine quaternary ammonium salt crosslinker, stir and react at 60°C for 8 hours, precipitate, filter, wash with water, and dry to obtain a functionalized water-absorbing chitosan material.

[0023] Example 2

[0024] S1. Add tetrahydrofuran, co-solvent water, 52 parts by weight of sodium hydroxide, 200 parts by weight of sodium 2-chloroethane sulfonate, and 100 parts by weight of 4-imidazolecarboxaldehyde into a reaction bottle, stir to dissolve, heat to 55° C. and react for 6 hours, concentrate to remove tetrahydrofuran, add hydrochloric acid solution to adjust the pH to 4, add saturated sodium chloride solution and ethyl acetate, extract and separate, concentrate the organic layer to remove ethyl acetate, and recrystallize the product in water to obtain 4-imidazolecarboxaldehyde chlorosulfonic acid intermediate.

[0025] S2. Add N,N-dimethylformamide, 100 parts by weight of cyanuric chloride, and 330 parts by weight of 4-imidazolecarboxaldehyde chlorosulfonic acid intermediate into a reaction bottle, stir and react at a temperature of 100° C. for 12 hours, concentrate to remove N,N-dimethylformamide, and recrystallize the product in ethanol to obtain an aldehyde triazine quaternary ammonium salt crosslinking agent.

[0026] Add 1.5% acetic acid solution and 100 parts by weight of chitosan to the reaction bottle, stir to dissolve, add 10 parts by weight of aldehyde triazine quaternary ammonium salt crosslinker, stir and react at 60°C for 6 hours, precipitate, filter, wash with water, and dry to obtain a functionalized water-absorbing chitosan material.

[0027] Example 3

[0028] S1. Add tetrahydrofuran, co-solvent water, 45 parts by weight of sodium hydroxide, 180 parts by weight of sodium 2-chloroethane sulfonate, and 100 parts by weight of 4-imidazolecarboxaldehyde into a reaction bottle, stir and dissolve, heat to 50°C and react for 6 hours, concentrate to remove tetrahydrofuran, add hydrochloric acid solution to adjust the pH to 2, add saturated sodium chloride solution and ethyl acetate, extract and separate, concentrate the organic layer to remove ethyl acetate, and recrystallize the product in water to obtain 4-imidazolecarboxaldehyde chlorosulfonic acid intermediate.

[0029] S2. Add N,N-dimethylformamide, 100 parts by weight of cyanuric chloride, and 360 parts by weight of 4-imidazolecarboxaldehyde chlorosulfonic acid intermediate into a reaction bottle, stir and react at a temperature of 100° C. for 18 hours, concentrate to remove N,N-dimethylformamide, and recrystallize the product in ethanol to obtain an aldehyde triazine quaternary ammonium salt crosslinking agent.

[0030] Add 2% acetic acid solution and 100 parts by weight of chitosan to the reaction bottle, stir to dissolve, add 15 parts by weight of aldehyde triazine quaternary ammonium salt crosslinking agent, stir and react at 75°C for 3 hours, precipitate, filter, wash with water, and dry to obtain a functionalized water-absorbing chitosan material.

[0031] Example 4

[0032] S1. Add tetrahydrofuran, co-solvent water, 52 parts by weight of sodium hydroxide, 180 parts by weight of sodium 2-chloroethane sulfonate, and 100 parts by weight of 4-imidazolecarboxaldehyde into a reaction bottle, stir and dissolve, heat to 50°C and react for 4 hours, concentrate to remove tetrahydrofuran, add hydrochloric acid solution to adjust the pH to 2, add saturated sodium chloride solution and ethyl acetate, extract and separate, concentrate the organic layer to remove ethyl acetate, and recrystallize the product in water to obtain 4-imidazolecarboxaldehyde chlorosulfonic acid intermediate.

[0033] S2. Add N,N-dimethylformamide, 100 parts by weight of cyanuric chloride, and 330 parts by weight of 4-imidazolecarboxaldehyde chlorosulfonic acid intermediate into a reaction bottle, stir and react at a temperature of 85° C. for 24 hours, concentrate to remove N,N-dimethylformamide, and recrystallize the product in ethanol to obtain an aldehyde triazine quaternary ammonium salt crosslinking agent.

[0034] Add 1% acetic acid solution and 100 parts by weight of chitosan to the reaction bottle, stir to dissolve, add 22 parts by weight of aldehyde triazine quaternary ammonium salt crosslinking agent, stir and react at 65°C for 8 hours, precipitate, filter, wash with water, and dry to obtain a functionalized water-absorbing chitosan material.

[0035] Example 5

[0036] S1. Add tetrahydrofuran, co-solvent water, 60 parts by weight of sodium hydroxide, 220 parts by weight of sodium 2-chloroethane sulfonate, and 100 parts by weight of 4-imidazolecarboxaldehyde into a reaction bottle, stir and dissolve, heat to 40°C and react for 10 hours, concentrate to remove tetrahydrofuran, add hydrochloric acid solution to adjust the pH to 4, add saturated sodium chloride solution and ethyl acetate, extract and separate, concentrate the organic layer to remove ethyl acetate, and recrystallize the product in water to obtain 4-imidazolecarboxaldehyde chlorosulfonic acid intermediate.

[0037] S2. Add N,N-dimethylformamide, 100 parts by weight of cyanuric chloride, and 400 parts by weight of 4-imidazolecarboxaldehyde chlorosulfonic acid intermediate into a reaction bottle, stir and react at a temperature of 85° C. for 18 hours, concentrate to remove N,N-dimethylformamide, and recrystallize the product in ethanol to obtain an aldehyde triazine quaternary ammonium salt crosslinking agent.

[0038] Add 1% acetic acid solution and 100 parts by weight of chitosan to the reaction bottle, stir to dissolve, add 30 parts by weight of aldehyde triazine quaternary ammonium salt crosslinking agent, stir and react at 75°C for 4 hours, precipitate, filter, wash with water, and dry to obtain a functionalized water-absorbing chitosan material.

[0039] Comparative Example 1

[0040] Add 1.5% acetic acid solution and 100 parts by weight of chitosan to the reaction bottle, stir to dissolve, add 5 parts by weight of glutaraldehyde, stir and react at 60° C. for 8 hours, precipitate, filter, wash with water, and dry to obtain chitosan material.

[0041] Add the chitosan material to distilled water and soak for 6 hours. Take out the chitosan material, wipe off the excess water on the surface, weigh it, and calculate the water absorption rate W, W = (m1-m) / m×100%. m1 is the mass of the chitosan material after water absorption, and m is the mass before water absorption.

[0042] Table 1 Water absorption test of chitosan material.

[0043] Water absorption (%) Example 1 265.4 Example 2 401.7 Example 3 354.2 Example 4 319.8 Example 5 244.0 Comparative Example 1 63.6

[0044] Each embodiment utilizes the aldehyde group of the aldehyde triazine quaternary ammonium salt crosslinking agent to crosslink with the amino group of chitosan, thereby grafting the hydrophilic quaternary ammonium salt and sulfonic acid into the chitosan material, significantly improving the hydrophilicity of chitosan. In addition, the aldehyde triazine quaternary ammonium salt crosslinking agent contains three aldehyde groups, which form a porous structure of a spatial crosslinking network with chitosan, and the water absorption rate is greatly increased.

[0045] Comparative Example 1 uses traditional glutaraldehyde as a cross-linking agent, does not contain hydrophilic quaternary ammonium salt and sulfonic acid group, and the water absorption rate of the chitosan material is low.

[0046] Dissolve potassium dichromate in water to make 200mL Cr2O7 2- Chitosan material was added to a solution with a concentration of 100 mg / L and stirred at 25°C until adsorption equilibrium was reached. The Cr2O7 content of the adsorbed solution was determined by atomic absorption spectrometry. 2- concentration, calculate the equilibrium adsorption capacity Q, Q = (C-C1) × V / m, C is Cr2O7 2- The initial concentration of C1 is the concentration of Cr2O7 after adsorption. 2- concentration, V is the solution volume, and m is the mass of chitosan material.

[0047] Table 2Cr2O7 2- Equilibrium adsorption capacity test.

[0048]

[0049]

[0050] Each embodiment uses the aldehyde group of the aldehyde triazine quaternary ammonium salt crosslinking agent to crosslink with the amino group of chitosan to form a porous structure of a spatial crosslinking network with a larger specific surface area, higher water absorption rate, and more adsorption sites. At the same time, it contains functional quaternary ammonium salt cationic groups that can react with Cr2O7 2- Negative ions form electrostatic interactions, which significantly improve the chitosan material's ability to resist Cr2O7 2- adsorption capacity.

[0051] Dissolve potassium dichromate in water to prepare 200 mL of Cu 2+ Chitosan material was added to a solution with a concentration of 100 mg / L and stirred at 25°C until adsorption equilibrium was reached. The Cu content of the adsorbed solution was determined by atomic absorption spectrometry. 2+ concentration, calculate the equilibrium adsorption capacity Q, Q = (C-C1) × V / m, C is Cu 2+ The initial concentration of Cu after adsorption is 2+ concentration, V is the solution volume, and m is the mass of chitosan material.

[0052] Table 3Cu 2+ Equilibrium adsorption capacity test.

[0053]

[0054] In each embodiment, the aldehyde group of the aldehyde triazine quaternary ammonium salt crosslinking agent is used to crosslink with the amino group of chitosan to graft the functional sulfonic acid group, nitrogen-rich triazine and imidazole structure to the chitosan material. The nitrogen atoms in the sulfonic acid group, nitrogen-rich triazine and imidazole structure can react with Cu 2+ The chitosan material can significantly enhance the copper ions and metal ions. 2+ equilibrium adsorption capacity.

[0055] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A method for preparing a functionalized water-absorbing chitosan material, characterized in that: The method comprises the following steps: adding acetic acid solution and chitosan into a reaction bottle, stirring and dissolving, adding an aldehyde triazine quaternary ammonium salt crosslinking agent, stirring and reacting, precipitating, filtering, washing, and drying to obtain a functionalized water-absorbing chitosan material; The structural formula of the aldehyde triazine quaternary ammonium salt cross-linking agent is:

2. The method for preparing the functionalized water-absorbing chitosan material according to claim 1, characterized in that: The mass of the aldehyde triazine quaternary ammonium salt cross-linking agent is 5-30% of the mass of chitosan.

3. The method for preparing the functionalized water-absorbing chitosan material according to claim 1, characterized in that: The reaction is carried out at a temperature of 60-75°C for 3-8 hours.

4. The method for preparing the functionalized water-absorbing chitosan material according to claim 2, characterized in that: The preparation method of the aldehyde triazine quaternary ammonium salt cross-linking agent comprises the following steps: S1. Add tetrahydrofuran, water, sodium hydroxide, sodium 2-chloroethane sulfonate, and 4-imidazolecarboxaldehyde to a reaction flask, stir and dissolve, heat to 40-55° C. and react for 4-10 hours, concentrate to remove tetrahydrofuran, add hydrochloric acid solution, and then extract and separate. Recrystallize the product to obtain 4-imidazolecarboxaldehyde chlorosulfonic acid intermediate; S2. Add N,N-dimethylformamide, cyanuric chloride and 4-imidazolecarboxaldehyde chlorosulfonic acid intermediate into the reaction bottle, stir to react, concentrate to remove N,N-dimethylformamide, and recrystallize to obtain aldehyde triazine quaternary ammonium salt crosslinking agent.

5. The method for preparing the functionalized water-absorbing chitosan material according to claim 4, characterized in that: The masses of sodium hydroxide and sodium 2-chloroethane sulfonate in S1 are 45-60% and 180-230% of the mass of 4-imidazolecarboxaldehyde respectively.

6. The method for preparing the functionalized water-absorbing chitosan material according to claim 4, characterized in that: Hydrochloric acid solution is added to the S1 to adjust the pH to 2-4.

7. The method for preparing the functionalized water-absorbing chitosan material according to claim 4, characterized in that: The mass of the 4-imidazolecarboxaldehyde chlorosulfonic acid intermediate in S2 is 330-400% of the mass of cyanuric chloride.

8. The method for preparing the functionalized water-absorbing chitosan material according to claim 4, characterized in that: The reaction in S2 is carried out at a temperature of 85-100° C. for 12-24 hours.

9. Use of the functionalized water-absorbing chitosan material obtained by the preparation method according to any one of claims 1 to 8 in sewage treatment.

Citation Information

Patent Citations

  • A method for preparing irradiation-initiated chitosan-based dual-network high-strength hydrogels and its application

    CN113150320B

Cited By

  • Preparation method of polyquaternium functionalized non-woven fabric

    CN121675226A